STUDENTS’ SATISFACTION OF DISTANCE EDUCATION SERVICES IN THE ISLAND AREAS (A CASE STUDY AT UPBJJ-UT TERNATE) - Anfas; Sudarwo, Raden; Umasugi, Mohbir; Hafel, Muhlis; Simabur, Lisda Ariani (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2020)
This study aims to determine the level of student satisfaction in the islands regarding distance education services. The population in this study are all UT’’s students spreaded across various regions in the province of North Maluku. The sampling method uses simple random sampling, as many as 74 students. Data collection is carried out through interviews with respondents with questionnaire aids whose questions relate to UT's level of expectation and service quality. The results show that: (1) of all aspects of distance education services organized by UPBJJ-UT Ternate, all of them had been categorized as very satisfying, where the highest level of satisfaction was that of general information services by 101.28% or in other words had exceeded student expectations. While teaching material services, although still in the category of very satisfying for students, the percentage of satisfaction level is lower than other service aspects which is 95.76%. (2) From all aspects of distance education services organized by UPBJJ-UT Ternate, teaching material services still have a level of gap between expectations and valuations conducted by students.